2007
DOI: 10.1136/ip.2007.016683
|View full text |Cite
|
Sign up to set email alerts
|

Child drowning deaths in Xiamen city and suburbs, People’s Republic of China, 2001–5

Abstract: Drowning deaths in children in Xiamen city and suburbs follow trends that are markedly different from patterns observed in other countries. Different prevention strategies may be required for preventing child drowning deaths in Xiamen and other developing regions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
44
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 22 publications
6
44
1
1
Order By: Relevance
“…This correlates with Fang et al's findings in China [4]. Parental education and close supervision by parents have already been examined in rural settings in some lowand middle-income countries including Bangladesh and China [3,4].…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…This correlates with Fang et al's findings in China [4]. Parental education and close supervision by parents have already been examined in rural settings in some lowand middle-income countries including Bangladesh and China [3,4].…”
Section: Introductionsupporting
confidence: 87%
“…Rahman et al stated that the risk of childhood drowning was 2.1 times greater for mothers who were illiterate compared with those who had a secondary or higher level of education [3]. This correlates with Fang et al's findings in China [4]. Parental education and close supervision by parents have already been examined in rural settings in some lowand middle-income countries including Bangladesh and China [3,4].…”
Section: Introductionmentioning
confidence: 81%
“…Drowning rates are highest among children and in rural areas (Fang et al, 2007;Quan & Cummings, 2003;Rahman et al, 2006;Sitthi-amorn et al, 2006). Providing swimming lessons is an important strategy to prevent childhood drowning (Brenner et al, 2009;Hyder, Borse et al, 2008;McIntosh, 2009;Rahman et al, 2010;World Health Organization, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Drowning is one of the most common causes of death among young children in developing countries in Asia, including Thailand (Fang et al, 2007;Hyder, Wali, Fishman, & Schenk, 2008;Linnan et al, 2007;Rahman, Giashuddin, Svanstrom, & Rahman, 2006;Sitthi-amorn et al, 2006). In 1999, a study of unintentional injury death among children aged 2-16 years in Thailand showed that 35% of deaths were due to drowning (13.1/100,000; Kozik et al, 1999).…”
mentioning
confidence: 99%
“…Drowning rates, rate ratios, and age-adjusted mortality rates also were calculated for drowning victims with bathtub drowning deaths excluded. Previous studies have excluded bathtub drowning deaths since bathtub drowning deaths are unlikely to be related to swimming or water safety skill (Brenner et al, 2009;Browne, Lewis-Michl, & Stark, 2003). As noted above, recent literature has demonstrated the importance of swimming and water safety skills in drowning prevention.…”
Section: Discussionmentioning
confidence: 99%